Phenological Observation in the Czech Republic - History and Present - Hajkova, Lenka; Nekovar, Jiri; Richterova, Dasa; Koznarova, Vera; Sulovska, Sona; Vavra, Ales; Vondrakova, Alena; Vozenilek, Vit (IntechOpen, 2012)
None